Toward development of generic inhibitors against the 3C proteases of picornaviruses. (10th December 2018) - Banerjee, Kamalika; Bhat, Ruchika; Rao, V. U. Bhaskara; Nain, Anshu; Rallapalli, Kartik Lakshmi; Gangopadhyay, Sohona; Singh, R. P.; Banerjee, Manidipa; Jayaram, Bhyravabhotla
Abstract : Development of novel antivirals, which requires knowledge of the viral life cycle in molecular detail, is a daunting task, involving extensive investments, and frequently resulting in failure. As there exist significant commonalities among virus families in the manner of host interaction, identifying and targeting common rather than specific features may lead to the development of broadly useful antivirals. Here, we have targeted the 3C protease of Hepatitis A Virus (HAV), a feco‐orally transmitted virus of the family Picornaviridae, for identification of potential antivirals. The 3C protease is a viable drug target as it is required by HAV, as well as by other picornaviruses, for post‐translational proteolysis of viral polyproteins and for inhibiting host innate immune pathways. Computational screening, followed by chemical synthesis and experimental validation resulted in identification of a few compounds which, at low micromolar concentrations, could inhibit HAV 3C activity. These compounds were further tested experimentally against the 3C protease of Human Rhinovirus, another member of the Picornaviridae family, with comparable results. Computational studies on 3C proteases from other members of the picornavirus family have indicated that the compounds identified could potentially be generic inhibitors for picornavirus 3C proteases. Abstract : The active site residues of 3C proteases show a significant intraspecies overlap among most common members of the picornavirus family. The similarity of the interacting residues could be utilized for designing broad‐range generic inhibitors against the 3C proteases of the picornavirus family.